(untitled) (مجلة ديالى للبحوث الانسانية, 2022)
The acrylamide monomer is photopolymerized by aqueous Suspension of TiO2 semiconductor (Anatase) at room temperature and light intensity (medium pressure mercury lamp.) of 19.44 mW/cm2. Several parameters were explored that affected the photopolyerization process in this system, and these are:-